Penggunaan Metode Syndicate Group untuk Meningkatkan Hasil Belajar Matematika Tentang Pengolahan Data Statistika pada Peserta Didik Kelas VI Sekolah Dasar - Samadi Samadi (Universitas Sebelas Maret, 2020)
Abstract. The purposes of this research are describing the using of Syndicate Group on the Mathematic learning about the Processing of Statistical Data on class of six from students of Gedangan Elementary School on the Second Semester 2019/2020 Year Academic and analyzing the using of Syndicate Group in improving learning results on the Mathematic learning about the Processing of Statistical Data on class of six from students of Gedangan Elementary School on the Second Semester 2019/2020 Year Academic. The place of this research is the six class of Gedangan Elementary School, Sub district of Rembang, Regency of Rembang. The conclusion of this research are 1) the using of Syndicate Group on the Mathematic learning about the processing of statistical data on six grade students of Gedangan Elementary School on the Second Semester 2019/2020 Year Academic are by formatting the syndicate freely and also standard-serially with getting difficult work sheet and 2) the using of Syndicate Group is improving the learning results on the Mathematic learning about the processing of statistical data on six grade students of Gedangan Elementary School on the Second Semester 2019/2020 Year Academic form unsatisfying category into satisfying category. Kata kunci: syndicate group, learning outcomes. mathematics, statistical data processing